The Renaissance of Proton Batteries. Issue 5 (1st February 2021) - Xu, Yunkai; Wu, Xianyong; Ji, Xiulei
Abstract : Proton, as a charge carrier, is most attractive due to its size and the associated advantages. Recently, reversible proton insertion in electrodes has emerged in electrochemical energy storage. Unlike the conventional understanding on pseudocapacitive proton storage, more focus is allocated to the topotactic structural changes. To date, different genres of electrode materials have been explored for proton storage. Proton batteries do not compete with nonaqueous batteries in energy density; the salient advantage of proton storage is its rate capability, which is associated with its tiny size and its nature of forming hydrogen bonding. The recent progress on Grotthuss proton storage is the high rate performance. Proton‐conducting electrolytes is another area of the future development of proton batteries. Herein, the recent efforts of this emerging field of batteries are highlighted. Abstract : Herein, the recent progress on proton batteries is discussed. The electrode materials in terms of their proton storage properties are discussed. Different proton electrolytes on their pros and cons are also addressed. Finally, a roadmap of the present and future proton battery research is provided.